Why tandem mass spectrometry for trace analysis: Concepts of tandem analytical techniques. (28th April 2022) - Yost, Richard A.
Abstract : Rationale: The triple quadrupole mass spectrometer, typically in combination with a gas or liquid chromatograph (GC/MS/MS and LC/MS/MS), is perhaps the most iconic example today of a tandem analytical instrument. Here I present the concepts of tandem or hyphenated techniques for trace analysis (that is, the detection and/or quantitation of one or more analytes present in a mixture at low levels). Methods: This tutorial presents the principles of tandem trace analytical techniques such as GC/MS/MS and LC/MS/MS, including the capabilities and requirements for such tandem techniques, the role of sensitivity and selectivity in tandem techniques, ways to assess the "informing power" of these techniques, and a comparison of tandem techniques with individual techniques at high resolution. These points are illustrated with several examples of trace analysis using tandem analytical techniques. Results: Several characteristics of the triple quadrupole have made it the "laboratory workhorse" for trace analysis, including the remarkable efficiency of the low‐energy collision‐induced dissociation (CID) process in a radiofrequency (RF)‐only multipole collision cell, the ease of computer control, and the capability for rapid scanning, rapid switching from mass to mass, and high transmission efficiency, enabling a wide variety of MS/MS scans. The efficiency of selected reaction monitoring means that triple quadrupoles dominate MS/MS for detection and quantitation of targeted compounds. Conclusions: This special issue addresses the intriguing question of how the triple quadrupole mass spectrometer progressed from "bleeding edge" to "the laboratory workhorse" over the last 40 years. This tutorial on the principles of tandem trace analytical techniques provides perspectives and insights into answering that question and should help educate the novice and stimulate the sophisticate.